HYBRIDITY IN POPULAR CULTURE: A TRANSNATIONAL ANALYSIS OF AMERICAN ADAPTATIONS OF JAPANESE MOVIES IN 21st CENTURY - Della Putri Febrina (Universitas Gadjah Mada, 2017)
American popular culture has developed from time to time in producing the products. In the progress, the popular product has been modified to satisfy the taste of the consumer and Hollywood is being the one of popular product maker which applied modifications in manufacturing movies; and the result of the development is hybridity seen in Hollywood movies.The journal is written under American Studies discipline, by applying transnational analysis as the basis of the study. Furthermore, the research also used the theory of hybridity in constructing the analysis which concerned about American adaptations of Japanese original movies, namely The Grudge, Hachi: A Dog’s Tale, and Godzilla. The method used in the journal is the qualitative research which comprises the library research by analyzing the three movies as the primary data and the information of the production as the secondary data.There are some conclusions met in the analysis. Being the first one is the three movies definitely adopt American and Japanese narratives and build a new sphere where the two nations living under the same frame. The adoption includes adoption of values, language, and iconic figure in Japan. Then, the second discussion which intended to see the changing of values and taste in Hollywood has resulted some conclusions that the Hollywood has power in shifting the values of the original movies which defined as eastern values to be the ones which related to American values and the three American adaptations in the journal trigger the emergence of American movies with Asian narratives. Keywords: Hybridity, transnational, Hollywood, movies, popular culture, adaptation